Developing a Ring-Based Optical Network Structure with Glass-Through Nodes - Caserta, Marco; Schwarze, Silvia; Voß, Stefan (Journal of Telecommunications and Information Technology, 2012)
An important issue in designing optical transport networks (OTN) is security. The concept of 1+1 protection requires to connect each origin-destination(OD)-pair by at least two node-disjoint paths. In the case of a single edge or node failure, the connection of all OD-pairs is maintained under 1+1 protection. On a ring, 1+1 protection is given naturally. Moreover, on rings, the routing effort is typically decreasing. These observations motivate the investigation of ring structures for OTN. When developing a ring structure for telecommunication networks, several subtasks can be identified. Ringshave to be designed, OD-pairs have to be assigned to rings, communication among rings has to be defined, a proper flow routing has to be chosen, and rings have to be dimensioned regarding flow capacity. In this paper, we address the first two issues, namely generation of rings and assignment of OD-pairs to rings. Our approach allows to distinguish active and non-active (glass-through) nodes in OTN. Active nodes are equipped with active routing hardware that weakens the optical signal and has impact on feasible ring lengths. Non-active nodes do not influence the optical signal. Although a consideration of active/non-active nodes is important in ring design, only a few references address this issue. We propose an algorithm for generating random ring candidates. Moreover, we present a mathematical model for the assignment of OD-pairs to rings subject to a feasible choice of active nodes. We test our methods using a case of Deutsche Telekom.